Pengaruh Konflik Peran Ganda Terhadap Kinerja Dengan Stres Kerja Sebagai Variabel Intervening - achmad rizal ubaidillah; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine: 1) The effect of dual role conflict on work stress of women PR workers Pakis Mas Malang, 2) The effect of dual role conflict on the performance of female PR workers Pakis Mas Malang, 3) The effect of work stress on the performance of women laborers Pakis Mas Malang, 4) The effect of dual role conflict on the performance of women PR workers Pakis Mas Malang with work stress as an intervening variable. This study uses a quantitative method with a descriptive approach. The researchers choose PR Pakis Mas Malang as a case study with a population of 165 people and a sample of 62 people. Data collection techniques using questionnaires with measurements using a Likert scale. Then, the data analysis techniques used are validity test, reliability test, normality test, multicolliniarity test, heterokedasticity test, path analysis, t hypothesis test and sobel test.Thus, the results of this study indicate that: 1) Dual role conflict has a significant effect on the performance of women PR workers. Pakis Mas Malang, 2) Job stress has a significant effect on the performance of women PR workers. Pakis Mas Malang, 3) work stress cannot be an intervening variable between conflicting dual roles towards work stress on women PR workers Pakis Mas Malang. Keywords: Performance, Dual Role Conflict, Work Stress.